Psychometric Properties of a Questionnaire on Reading Behavior and Family Socialization - Micaela Sánchez Martín; José David Cuesta Sáez de Tejada; Tomás Izquierdo Rus (Universidad Autónoma de Baja California, 2022)
A number of factors are associated with students' reading habit, and family and school environments are among the most important contexts for the socialization of reading. The focus of this study is to determine the psychometric properties of a questionnaire to identify the main variables that support the adoption of a reading habit in primary education, analyze reading behavior based on books read, and corroborate the predictive model for reading behavior using a linear regression model. Based on a non-experimental, cross-sectional quantitative approach, the instrument was validated by analyzing data from 403 primary education students from the region of Murcia (Spain), and the construct validity was determined through factor analysis and by validating its consistency and reliability. The results obtained indicate that the instrument constructed has consistent psychometric indicators for the purpose it aims to serve.